(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
English is an international language which is used officially all around the world. English can connect society with the full world. Everyone who wants to make connections with the world should learn English. In our country learn English is necessary to reach some targets. To make English as a second language in our life, we need to understand the basis of English and appropriate learning strategy. A lot of information in the world is written in English.